Audio material as part of the local history collection at the public library – a case study of radio program by Ivan Herman (Libellarium: journal for research in the field of information and related sciences, 2016)
The paper presents and analyses the laws and other legal documents as well as standards, guidelines and codes of library profession related to the local history collection creation and development at the public library. The Croatian laws on electronic media and copyright are also analysed because the paper describes the case study of audio materials which were created as part of the radio program of the local radio station. Such materials are local in nature and therefore surely belong to the local history library collection. Since this type of material is not directly regulated in legislation, the paper offers a starting point for such cases to be included in public libraries local history collections. The case study shows the destiny of radio program named U četiri ćoška by Ivan Herman which was aired on the Croatian Radio Županja.lyses the laws and other legal documents as well as standards, guidelines and codes of library profession related to the local history collection creation and development at the public library. The Croatian laws on electronic media and copyright are also analysed because the paper describes the case study of audio materials which were created as part of the radio program of the local radio station. Such materials are local in nature and therefore surely belong to the local history library collection. Since this type of material is not directly regulated in legislation, the paper offers a starting point for such cases to be included in public libraries local history collections. The case study shows the destiny of radio program named U četiri ćoška by Ivan Herman which was aired on the Croatian Radio Županja.
Keywords: public library; local history collection; audio material; radio; radio program